2016
DOI: 10.1017/s0007114516004189
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of an oxylipin-containing lyophilised biomass from a microalga in a murine recurrent colitis model

Abstract: Diet and nutritional factors have emerged as possible interventions for inflammatory bowel diseases (IBD), which are characterised by chronic uncontrolled inflammation of the intestinal mucosa. Microalgal species are a promising source of n-3 PUFA and derived oxylipins, which are lipid mediators with a key role in the resolution of inflammation. The aim of the present study was to investigate the effects of an oxylipin-containing lyophilised biomass from Chlamydomonas debaryana on a recurrent 2,4,6-trinitroben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…Extracts of Tetraselmis suecica [14], Chlorella ovalis, Nannochloropsis oculata, and Amphidinium carterae [13], and a sterol-rich fraction of Nannochloropsis oculata [15] were active in LPS-stimulated RAW 264.7 macrophages. Oxylipin-containing lyophilized biomass from Chlamydomonas debaryana have been shown to have anti-inflammatory properties in an induced colitis rat model [16][17][18] and Dunaliella bardawil was found to protect against acetic acid-induced small bowel inflammation in rats [16,17]. Regarding studies on LPS-stimulated human THP-1 monocytic leukemia cells, lipid extracts of Pavlova lutheri [19] and monogalactosyldiacylglycerols (MGDGs) and digalactosyldiacylglycerols (DGDGs) mixtures, and the isolated DGDGs 11 and 12 from Isochrysis galbana [20] were reported as active.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of Tetraselmis suecica [14], Chlorella ovalis, Nannochloropsis oculata, and Amphidinium carterae [13], and a sterol-rich fraction of Nannochloropsis oculata [15] were active in LPS-stimulated RAW 264.7 macrophages. Oxylipin-containing lyophilized biomass from Chlamydomonas debaryana have been shown to have anti-inflammatory properties in an induced colitis rat model [16][17][18] and Dunaliella bardawil was found to protect against acetic acid-induced small bowel inflammation in rats [16,17]. Regarding studies on LPS-stimulated human THP-1 monocytic leukemia cells, lipid extracts of Pavlova lutheri [19] and monogalactosyldiacylglycerols (MGDGs) and digalactosyldiacylglycerols (DGDGs) mixtures, and the isolated DGDGs 11 and 12 from Isochrysis galbana [20] were reported as active.…”
Section: Introductionmentioning
confidence: 99%
“…During the inflammatory processes, the OS plays an important role in promoting its maintenance throughout time. In this condition, there are well-established increases of Nrf-2 expression and the consecutive regulation of the expression of numerous cytoprotective genes encoding antioxidant enzymes, such as ferritin, superoxide dismutase (SOD), peroxiredoxin-1 (PRDX1) and gluthathione S-tranferases (GSTs) [ 13 , 55 ], and also its downstream target, HO-1, to ameliorate the oxidative effects [ 56 , 57 ]. In our study, an Nrf-2 and HO-1 up-regulation was observed in the CD Group, indicating the primary events of acute inflammation, probably as a compensatory system to alleviate inflammation and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an Nrf-2 and HO-1 up-regulation was observed in the CD Group, indicating the primary events of acute inflammation, probably as a compensatory system to alleviate inflammation and tissue damage. On the contrary, Ávila-Román et al [ 57 ] demonstrated reduced Nrf-2 and HO-1 expression levels in colon samples from a TNBS chronic colitis model. In addition, several dietary phytochemicals, such as green tea polyphenol components [ 58 ], anthocyanins [ 59 ] and carotenoids [ 56 ], have been implicated in reversing inflammatory processes by increasing the expression of Nrf-2 and HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…In the dextran sulphate sodium (DSS)-induced colitis mouse model, the enhanced expression of Nrf-2 and HO-1 were detected under colitis wound repair [50]. In the 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis mouse model, oral administration of lyophilized microalgal biomass from Chlamydomonas debaryana up-regulated the expressions of Nrf-2 and HO-1 [51]. In the present study, we observed that 1 markedly promoted the nuclear translocation of Nrf2 and subsequent increase in the expression of HO-1.…”
Section: Discussionmentioning
confidence: 99%